Evidence of Absence or Absence of Evidence? Searching for Late Mesolithic (Castelnovian) Hunter-Gatherers in the Eastern Adriatic - Kačar, Sonja (Journal of Mediterranean Archaeology, 2021)
The last hunter-gatherers of the central and western Mediterranean are associated with the Castelnovian technocomplex, which developed during the seventh millennium BC and is characterized mainly by its lithic industries, which reflect important changes that occurred during the Late Mesolithic: debitage from this time is oriented towards blade production by pressure-flaking and the manufacture of special tools, such as trapezes (made by the microburin technique) and notched blades. Although rare, Castelnovian sites have been identified in the wider Adriatic region of south-central Italy, Albania, Montenegro and the Italian and Slovenian Karst. However, it seems that the Croatian coast and its hinterland in the eastern Adriatic lack any traces. No sites were found in Dalmatia and only a few questionable surface finds come from Istria. This study explores whether this absence is due to historical factors, such as depopulation during the Late Mesolithic or the region being outside the Castelnovian expansion route, or whether it is because of a combination of taphonomic causes (such as loss of sites by marine transgression) and lack of previous research. The paper also focuses on the hypothesis that the presence of the last hunter-gatherers can be detected indirectly through the persistence of Castelnovian elements in the oldest Neolithic Impressed Ware assemblages of the eastern Adriatic. I further propose that Castelnovian traits are observable in the Impressed Ware assemblages of Istria. This Mesolithic tradition consists of the use of local flint, blade production by indirect percussion and ‘simpler’ forms of pressure flaking in lithic production, while marine resources remain an important food resource.